Os tons em trânsito de Clara Nunes: samba, carnaval e religião (1966-1984) - Pastro, Tamara Claudia Coimbra (2018)
The present work aims to understand the trajectory of the singer Clara Nunes (1942-1983) and her insertion within the Brazilian music scene. From the analysis of her career in four moments, this work seeks to understand how she can establish a prominent place resulting in commercial success. From the analysis of her records, her transits with Afro-Brazilian culture are observed, reaffirming her cultural identity and identifying the reflexes of this process in the consolidation of her career in the Brazilian phonographic scene. To achieve this, two themes were chosen that permeate her artistic life: carnival and religiosity. In a constant interlocution between sacred and profane each takes its place within a political discourse and a social practice. The singer knew how to relate different ways to become an icon of Brazilian popular music, following her steps, this work makes a plural journey to understand its object based on its initiatives and different possibilities.